Climate change impacts on the Copernicia alba and Copernicia prunifera (Arecaceae) distribution in South America - Costa, Marcones Ferreira; Francisconi, Ana Flávia; Vancine, Maurício Humberto [UNESP]; Zucchi, Maria Imaculada (Springer Nature, 2022)
Climate changes are one of the main factors that affect palm trees distribution in the tropics. Among the palm trees with social, economic, and ecological relevance, we highlight the native species, Copernicia alba Morong ex Morong and Britton and Copernicia prunifera (Miller) H. E Moore. An important strategy for protecting biodiversity is to identity the climate areas that will be suitable for future habitats of the species. In this sense, we used the ecological niche models (ENMs) to predict the suitable climate areas for the potential occurrence of C. alba and C. prunifera palm trees in current and future scenarios, RCP 4.5 (optimistic) and 8.5 (pessimistic), besides to evaluate these species vulnerability facing the climate changes. Our results predicted the C. prunifera habitat would continue to increase over the past years. In the RCP 8.5 scenario, the climate model projected an increase of 23.88% for the C. prunifera population between 2050 and 2070. Also, our results can be used for the application and the establishment of commercial C. prunifera plantations. By contrast, the predicted habitat of C. alba will decrease 22.2% between 2050 and 2070, according to the RCP 8.5 scenario. For both C. prunifera and C. alba species, we observed a low percentage of the potential distribution in protected areas for future scenarios. Therefore, we suggest the creation and maintenance of extensive forestry Protected Areas (PAs) with ecological corridors and the construction of germplasm banks to manage and conserve these two important palm tree species.
Keywords: Caranda; Carnauba palm; Conservation; Ecological niche models